2013
DOI: 10.1107/s1600576713028665
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved grazing-incidence time-of-flight neutron scattering from a solid–liquid interface

Abstract: Small‐angle scattering in grazing‐incidence beam geometry has been applied on a time‐of‐flight neutron instrument to investigate a solid–liquid boundary. Owing to the broad wavelength distribution provided for a specific incident beam angle, the penetration depth of the neutron beam is varied over a wide range in a single measurement. The near surface structures of block copolymer micelles close to silicon substrates with distinct surface energies are resolved. It is observed that the very near surface structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Temperatures close to ambient also avoid excessive evaporation or condensation of the water, which would change the polymer concentration during the measurements. It has been reported that the properties of the interfacial layer of the polymer solution depend strongly on the surface treatment of the substrate (Wolff et al, 2005(Wolff et al, , 2014. Additionally, pre-crystallization at the liquid-solid interface has been observed (Gerstenberg et al, 1998).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Temperatures close to ambient also avoid excessive evaporation or condensation of the water, which would change the polymer concentration during the measurements. It has been reported that the properties of the interfacial layer of the polymer solution depend strongly on the surface treatment of the substrate (Wolff et al, 2005(Wolff et al, , 2014. Additionally, pre-crystallization at the liquid-solid interface has been observed (Gerstenberg et al, 1998).…”
Section: Samplementioning
confidence: 99%
“…The sample was stirred by a magnetic stirrer at this low temperature until a homogeneous transparent solution formed (Song et al, 2000). It is important to note that this sample is known to have a large scattering contrast for neutron scattering studies if solved in heavy water (Mortensen, 1996;Jiang et al, 2007;Wolff et al, 2013), together with interesting surface and shear properties (Hyun et al, 2006;Wolff et al, 2014).…”
Section: Samplementioning
confidence: 99%
“…Figure 6. Left panel: GISANS scattering pattern plotted on the surface of the Ewald sphere in three dimensions [18]. Right panel: Reciprocal lattice for a cubic close packing (ccp).…”
Section: Off-specular and Gisansmentioning
confidence: 99%
“…0.175 mm for a 5 cm sample under the angle of 0.2 • is small. Figure 11 depicts patterns of intensity measured on SANS-2D (Rutherford Institute, Didcot, England) for the polymer solution discussed above but now in contact to two silicon wafers with distinct surface energies [18]. The incident beam was collimated to provide a divergence of 0.29 • and 0.04 • along y and z direction, respectively.…”
Section: Modes Of Measurementmentioning
confidence: 99%
“…In the majority of the studies (Mü ller-Buschbaum et al, 2008;Als-Nielsen et al, 1994;Prieve & Walz, 1993;Dosch et al, 1986;Wolff et al, 2014;Al-Hussein et al, 2013;Parratt, 1954;Dietrich & Wagner, 1984;Gutfreund, 2011), the penetration depth can be expressed as…”
Section: Theorymentioning
confidence: 99%